PENERAPAN MODEL PROBLEM BASED LEARNING (PEMBELAJARAN BERBASIS MASALAH) UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA - F. Kurnia Nirmala Sari (Kurikula : Jurnal Pendidikan, 2022)
This study aims to determine the effect Problem Based Learning model on student’s critical thinking skills. The research methos used is a control group pretest-posttest design that uses the N-Gain test to analiyze data on student’s critical thinking skills. The sample used in this study was obtained by using cluster random sampling technique from the population of grade X SMA Negeri 2 Ngawi. The esperimental class N-Gain test result are 0,68 and are in the medium category, anthe control class has N-Gain value 0f 0,53 and is also is the medium category, but the experimental class N-Gain is treather than the control class, so thah this research can be said that the application of the Problem Based Learning (PBL) learning model has a significant influence on student’s critical thinking skills.